2011
DOI: 10.1101/gr.121897.111
|View full text |Cite
|
Sign up to set email alerts
|

Sequence shortening in the rodent ancestor

Abstract: Insertions and deletions (indels), together with nucleotide substitutions, are major drivers of sequence evolution. An excess of deletions over insertions in genomic sequences-the so-called deletional bias-has been reported in a wide range of species, including mammals. However, this bias has not been found in the coding sequences of some mammalian species, such as human and mouse. To determine the strength of the deletional bias in mammals, and the influence of mutation and selection, we have quantified indel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 51 publications
9
20
0
Order By: Relevance
“…S2 and Dataset S4). Microdeletions are slightly smaller in size in human and macaque than in mouse and rat (by 0.46 bp on average), which is in agreement with a previous study (63). In summary, we observe substantial variation in the rate and size spectrum of DNA microdeletion between and within eutherian and avian orders.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S2 and Dataset S4). Microdeletions are slightly smaller in size in human and macaque than in mouse and rat (by 0.46 bp on average), which is in agreement with a previous study (63). In summary, we observe substantial variation in the rate and size spectrum of DNA microdeletion between and within eutherian and avian orders.…”
Section: Resultssupporting
confidence: 92%
“…5A), about 3.5× higher as those for the human lineage, in agreement with previous analyses of a smaller number of mammals (29,36,37,62,63). All other mammalian lineages we analyzed exhibit microdeletion rates that are intermediate between those of human and rodents, except for the common ancestor of bats (Chiroptera), which displays the lowest microdeletion rate in our analysis.…”
Section: Resultssupporting
confidence: 91%
“…It is consistent with the previously reported rodent lineage deletion bias (Laurie et al 2012) and demonstrates that this bias applies to transcriptional regulatory sequence to at least the same extent as protein-coding sequence (Taylor et al 2004).…”
Section: Resultssupporting
confidence: 80%
“…1D). This is consistent with reports of genome-wide excess deletions early in the rodent lineage (Laurie et al 2012). The deletion excess in rodents may also explain more subtle differences between human and mouse promoter evolution.…”
Section: Frequent Promoter Turnover In Mouse and Humansupporting
confidence: 81%
“…We have previously found that, in alignments of orthologous mammalian proteins, both amino acid tandem repeats and LCRs are more often associated with insertions than with deletions [27], suggesting that repetitive regions have a greater tendency to expand than to contract. The accumulation of certain LCRs over time will depend on the intrinsic rate of slippage of the triplets encoding the underlying amino acid repeats, as well as the strength and mode of selection acting on the LCRs.…”
Section: Introductionmentioning
confidence: 99%